Nutritional modulation of the antioxidant capacities in poultry: the case of vitamin E. (26th February 2019) - Surai, Peter F; Kochish, Ivan I; Romanov, Michael N; Griffin, Darren K
ABSTRACT: Commercial poultry production is associated with a range of stresses, including environmental, technological, nutritional, and internal/biological ones, responsible for decreased productive and reproductive performance of poultry. At the molecular level, most of them are associated with oxidative stress and damages to important biological molecules. Poultry feed contains a range of feed-derived and supplemented antioxidants and, among them, vitamin E is considered as the "headquarters" of the antioxidant defense network. It is well-established that dietary supplementation of selenium, vitamin E, and carotenoids can modulate antioxidant defenses in poultry. The aim of the present paper is to present evidence related to modulation of the antioxidant capacities in poultry by vitamin E. Using 3 model systems including poultry breeders/males, semen, and chicken embryo/postnatal chickens, the possibility of modulation of the antioxidant defense mechanisms has been clearly demonstrated. It was shown that increased vitamin E supplementation in the breeder's or cockerel's diet increased their resistance to various stresses, including high polyunsaturated fatty acids (PUFA ), mycotoxin, or heat stress. Increased vitamin E supplementation of poultry males was shown to be associated with significant increases in α-tocopherol level in semen associated with an increased resistance to oxidative stress imposed by various external stressors. Similarly, increased vitamin E concentration in the egg yolk due to dietary supplementation was shown to be associated with increased α-tocopherol concentration in the tissues of the developing embryos and newly hatched chicks resulting in increased antioxidant defenses and decreased lipid peroxidation. Furthermore, increased vitamin E transfer from the feed to egg yolk and further to the developing embryo was shown to be associated with upregulation of antioxidant enzymes reflecting antioxidant system regulation and adaptation. The role of vitamin E in cell signaling and gene expression as well as in interaction with microbiota and maintaining gut health in poultry awaits further investigation.